Advances in library administration and organization. Vol. 21 - Garten, Edward D.; Williams, Delmus Eugene; Nyce, James (Emerald, 2004)
Volume twenty one of Advances in Library Administration and Organization offers timely articles from scholars and administrators working throughout the world. It adapts theory to practice in a variety of areas of interest to those who manage libraries. These include a demographic study of Canadian librarianship, an article on the implementation of ISO9000 in Thailand, pieces on information literacy programs in the United States, and a discussion of organizational culture within libraries from South Africa. The idea is to provide food for thought for practitioners and theorist alike so that they might be spurred to think about the challenge of making libraries run well. Whether one is interested is service philosophies as discussed in a symposium held in honor of Johannah Sherrer, the definition of command work, or the process used to thoughtfully develop and refine an assessment program in a Colorado university library, there is something here for every manager that will help them confront the challenges facing them. The articles address obstacles facing all of us every day and offer insights that can be of value as we seek a vision for libraries and librarianship in the 21st century.
Keywords: Language Arts & Disciplines -- Library & Information Science -- General.; Library, archive & information management.; Library administration.; elektronické knihy; electronic books